The wind from the east : French intellectuals, the cultural revolution, and the legacy of the 1960s - Wolin, Richard (Princeton University Press : Princeton University Press, 2018)
Combining a merciless exposé of left-wing political folly and cross-cultural misunderstanding with a spirited defense of the 1960s, this book tells the colourful story of this legendary period in France.
Keywords: Mao, Zedong, -- 1893-1976 -- Influence.; Mao, Zedong, -- 1893-1976; Intellectuals -- France -- History -- 20th century.; Intellectuals -- Political activity -- France -- History -- 20th century.; France -- Intellectual life -- 20th century.; Communism -- France -- History -- 20th century.; China -- History -- Cultural Revolution, 1966-1976 -- Influence.; Intellectuels -- France -- Histoire -- 20e siècle.; Intellectuels -- Activité politique -- France -- Histoire -- 20e siècle.; France -- Vie intellectuelle -- 20e siècle.; Chine -- Histoire -- 1966-1976 (Révolution culturelle) -- Influence.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; HISTORY -- Europe -- France.; Communism; Influence (Literary, artistic, etc.); Intellectual life; Intellectuals; Intellectuals -- Political activity; China; France; 1900-1999; History